Bounded and Invertible Toeplitz Products on Vector Weighted Bergman Spaces of the Unit Polydisc - Gbogbo, F.; Otoo, S.D.; Asomaning, O.; Huago, R.Q. (Environmental Monitoring and Assessment, 2017)
Fish and shellfish are regularly consumed and sold in Ghana, yet studies on arsenic pollution in Ghana are limited largely to ground water. This study evaluated arsenic concentrations in seven species of shellfish and 10 species of fish inhabiting the mouth of Ankobra, Densu and Volta basins in Ghana and assessed the public health implications. Arsenic levels varied from 0.2 to 2.2 mg L−1 in the three rivers and were higher than WHO recommended values of 10 μg L−1 for drinking water. Except for Periophthalmus sp. and Tympanotonus fuscatus from the Ankobra in which arsenic was not detected, concentrations in the organisms ranged from 0.2 to 2.8 mg kg−1. The maximum quantities of the organisms considered safe for consumption ranged from 375 to 5250 g per week. Caution however needs to be exercised as PTWI for arsenic needs revision, and some heavy metals such as mercury are more toxic than arsenic.
Keywords: Arsenic; Fish; Pollution; Shellfish; Wetlands